Flavonols from Pterogyne nitens and their evaluation as myeloperoxidase inhibitors - Regasini, Luis Octavio [UNESP]; Rebuglio Vellosa, Jose Carlos [UNESP]; Siqueira Silva, Dulce Helena [UNESP]; Furlan, Maysa [UNESP]; Mascarenhas de Oliveira, Olga Maria [UNESP]; Khalil, Najeh Maissar [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Marx Young, Maria Claudia; Barreiro, Eliezer Jesus; Bolzani, Vanderlan da Silva [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
A myeloperoxidase inhibitory kaempferol derivative, namely pterogynoside (1), was isolated from fruits of Pterogyne nitens, along with six known flavonols, kaempferol, afzelin, kaempferitrin, quercetin, isoquercetrin and rutin. The structures of all compounds were elucidated primarily from 1D and 2D NMR spectroscopic analyses, as well as by high resolution mass spectrometry. All flavonols were screened to identify secondary metabolites as potential myeloperoxidase (MPO) inhibitors, and at concentrations of 0.50-50 nM, quercetin (5), isoquercitrin (6) and rutin (7) exhibited strong inhibitory effects with IC(50) values of 1.22 +/- 0.01, 3.75 +/- 0.02 and 3.60 +/- 0.02, respectively. The MPO activity detected for the new derivative 1 was markedly decreased (IC(50) 10.3 +/- 0.03) when compared with known flavonols 5-7, and interestingly increased when tested against ABTS scavenging activity. (C) 2008 Published by Elsevier Ltd.
Keywords: Pterogyne nitens; Fabaceae; acylated flavonol; myeloperoxidase; antioxidant